The Effect of Ethical Leadership On Job Performance: The Mediating Role of Public Service Motivation and Normative Commitment - Muchlis Syahrani; Hernawaty Hernawaty; Alex Winarno (Journal of Leadership in Organizations, 2022)
Introduction/Main Objectives: To analyze how ethical leadership influences job performance mediated public service motivation and normative commitment in public institutions.  Background Problems: Ethical issues in public institutions are rarely discussed openly by involving practitioners, although ethical issues are the root of the emergence of various problems in public organizations.  Leaders play an important role in ethics. Novelty: Show ethical leadership as a resource for social learning and provide an understanding that ethical leadership is an important leadership style in the job performance system of public services in leader-member exchange theory. Research Methods: The explanation method uses a survey of 327 civil servants in East Kalimantan. The data analysis technique uses SEM covariance.  Finding/Results: Ethical leadership as a model for subordinates in providing public services. The interaction between leaders and subordinates encourages public service motivation for the public and fosters normative commitment based on consideration of ethical values. Ethical leaders influence the job performance of civil servants through service and normative commitment. Conclusion: Increased public service motivation and normative awareness, as well as job performance as a public servant, is influenced by ethical leadership. The practical implication is the need to develop and strengthen interactions between leaders and subordinates as a social learning process that can activate ethical awareness as public servants.